2004
DOI: 10.1063/1.1801271
|View full text |Cite
|
Sign up to set email alerts
|

A reactive force field simulation of liquid–liquid phase transitions in phosphorus

Abstract: A force field model of phosphorus has been developed based on density functional ͑DF͒ computations and experimental results, covering low energy forms of local tetrahedral symmetry and more compact ͑simple cubic͒ structures that arise with increasing pressure. Rules tailored to DF data for the addition, deletion, and exchange of covalent bonds allow the system to adapt the bonding configuration to the thermodynamic state. Monte Carlo simulations in the N-P-T ensemble show that the molecular (P 4 ) liquid phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…In this case, the formation of the red phosphorus polymers of both linear and three-dimensional structure is possible. Experimental data [9] and Monte Carlo simulations [10] have shown that the P 4 liquid phase, while being stable at low pressure, P, and relatively low temperature, T, transforms to a polymeric state by increasing either P or T. These phase changes were observed in recent experiments with similar thermodynamic conditions, as shown by a close agreement of computed and measured structure factors in the molecular and polymer phases [10].…”
Section: Introductionmentioning
confidence: 65%
“…In this case, the formation of the red phosphorus polymers of both linear and three-dimensional structure is possible. Experimental data [9] and Monte Carlo simulations [10] have shown that the P 4 liquid phase, while being stable at low pressure, P, and relatively low temperature, T, transforms to a polymeric state by increasing either P or T. These phase changes were observed in recent experiments with similar thermodynamic conditions, as shown by a close agreement of computed and measured structure factors in the molecular and polymer phases [10].…”
Section: Introductionmentioning
confidence: 65%
“…The phosphorus and carbon atoms were modeled as uncharged Lennard-Jones particles. The cross sections r for phosphorus and carbon atoms are r pp = 3.33 Å [7] and r cc = 3.4 Å [8], respectively. The depth of potential well for phosphorus and carbon atoms are e pp = 0.400 kcal/mol [7] and e cc = 0.086 kcal/mol [8], respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The cross sections r for phosphorus and carbon atoms are r pp = 3.33 Å [7] and r cc = 3.4 Å [8], respectively. The depth of potential well for phosphorus and carbon atoms are e pp = 0.400 kcal/mol [7] and e cc = 0.086 kcal/mol [8], respectively. The bond strength constants for phosphorus and carbon atoms are 297 kcal mol À1 Å 2 [7] and 938 kcal mol À1 Å 2 [8], respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that the open structures could be interpreted as a modulation of random packing by oscillations in the effective potentials. Ballone and Jones 26 studied the liquid-liquid phase transition in a 4000 atom sample of P using a classical force field fit to an extensive set of density functional (DF) calculations on phosphorus clusters. The first molecular dynamics (MD)/DF simulation of liquid Bi was performed by de Wijs et al 27 on a 60-atom sample over 4.15 ps at 1000 K. Souto et al 28 carried out simulations at 600 K (124 atoms, 600 K, 40 ps, local density approximation for exchange and correlation) and discussed the static and dynamical structure factors, the pair distribution function, and the nature of the collective modes.…”
Section: Introductionmentioning
confidence: 99%